Keadilan Restoratif bagi Anak Pelaku Tindak Pidana yang Dilakukan Bersama Orang Dewasa: Dilema Antara Pembinaan dan Pemidanaan - Nur Sri Maryam Dm; Budiyanto (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
This article examines the application of restorative justice principles to juvenile offenders who commit crimes alongside adults within the Indonesian criminal justice system. This research begins with two research questions: how the principles of restorative justice are applied to juvenile offenders who commit crimes alongside adults within the Indonesian criminal justice system, and how law enforcement officers navigate the dilemma between guidance and punishment when dealing with juveniles involved in crimes with adult offenders. This research employs a normative juridical approach using a qualitative descriptive method, involving an analysis of legal norms, principles, and doctrines related to child protection in criminal law. The findings indicate that the implementation of diversion and restorative justice continues to face various challenges, particularly when crimes involve adult offenders processed through the general justice system. This situation creates a dilemma for law enforcement officers between enforcing the law through punishment and fulfilling the state’s obligation to protect and guide children in accordance with the principle of the best interests of the child. Therefore, it is necessary to separate the handling of cases involving juvenile and adult offenders and to strengthen the capacity of law enforcement officials in implementing a restorative approach that balances legal certainty, justice, and humanity.